NEW OBSERVATION OF ROCINELA SIGNATA SCHIOEDTE & MEINERT, 1879 (ISOPODA: AEGIDAE) AS ECTO- AND GILL PARASITE OF RED SNAPPER FISH LUTJANUS PURPUREUS (POEY, 1866), COLLECTED FROM THE GREAT AMAZON REEF SYSTEM (GARS) (Environmental Smoke, 2023)
The isopod Rocinela signata Schioedte & Meinert, 1879 (Aegidae) is largely recorded in literature as ectoparasites of marine fishes; however, the full list of hosts is still far from complete. We report the occurrence of R. signata as ectoparasite from a new host: Lutjanus purpureus (Poey, 1866), an important fishery resource in the northern region of Brazil, collected from the Great Amazon Reef System (GARS), Brazil. Four specimens of R. signata were observed parasitizing three specimens of L. purpureus, collected during the fishery operations, using a manzuá trap along the continental shelf of the Amapá State. The presence of R. signata in the GARS expands its geographic distribution (the northernmost Brazilian record), additionally, the occurrence of R. signata in deeper waters than previously reported (~90 m), and its new host interaction.